Plan de negocios, mediante la aplicación del método Canvas, para proponer la creación de la empresa de eventos y banquetes “El ensueño de tu vida”, en el barrio Amazonas del cantón Joya de los Sachas - Puglla Morejón, Sandra Patricia (2016)
This was conducted in the Canton of La Joya Sacha, seeing the need for people to not have a ballroom and banquet where they can make proper reception of the different social, public and private events; must rent reception rooms that do not have adequate infrastructure, service and comfort needed to develop the events. For this reason it has been the need to create a business event and banquets "THE DREAM OF YOUR LIFE" it will improve how to perform different types of events The research process that was used for the project was the situational analysis study of the area to know how you are and where you will carry out the project investigating factors such as natural and cultural, demographic analysis, economic diagnosis. After analyzing the feasibility of the situational study area we proceeded to develop the business plan by obtaining important results KEDS methodology such as financial analysis, financing sources and calculation of total investment of $ 178,990.24; the amount of income from services is $ 1'705.744,47 year, demonstrating that the project is feasible. Distribution channels, product strategy, key partners. With the information obtained we proceeded to identify the creation of the company and the area requirement, location determination, implementation of quipment and materials, physical distribution room (flat). Thereby safeguarding the good customer.